Can a partnership between general practitioners and ambulance services reduce conveyance to emergency care?. Issue 7 (18th April 2017) - Villarreal, Manuel; Leach, Jonathan; Ngianga-Bakwin, Kandala; Dale, Jeremy
Abstract : Background: Emergency services are facing increasing workload pressures, and new models of care are needed. We evaluate the impact of a service development involving a partnership between emergency ambulance crews and general practitioners (GPs) on reducing conveyance rates to the Hospital Emergency Department(ED) . Methods: The service model was implemented in the West Midlands of England. Call handlers identified patients with needs that could be addressed by a GP using locally agreed criteria. GPs supported the assessment of such patients either at scene or by telephone. Routine data were collected from October 2012 to November 2013, from the ambulance service computer-aided dispatch system. Logistic regression models were used to determine the likelihood for patients being transported to ED. Results: Of 23 395 emergency contacts during the evaluation period, 1903 (8.1 %) patients were triaged to GP supported assessment. Mean age (SD) was 61.8 (27.9) years; 42.9 % were aged 75 years and over. 1221 (64.2%) had face-to-face GP assessment and 682 (35.8%) via telephone. 1500 (78%) of those who received GP support were not transported to hospital. After controlling for confounders, those aged greater than 75 years (OR 0.67; 95% CI 0.52 to 0.86), and females (OR 0.64; 95% CI 0.51 to 0.82) were less likely to be transported, while those who received GP telephone input rather than face-to-face assessment were more likely to be transferred to an ED (OR 2.14; 95% CI 1.69 to 2.72). Conclusion: Support of the paramedic service by GPs enabled patients to avoid transfer to an ED, potentially avoiding subsequent hospital admission, reducing costs and improving quality of care for patients that are not in need of hospital services. However, use of services in the days following the call was not assessed, and hence the overall impact and safety requires further evaluation.